In vitro study: Soybean meal substitution with maggot on sheep digestibility and rumen fermentation - Lilis Khotijah; Putri Sri Rahayu; Dewi Apri Astuti; Rima Shidqiyya Hidayati Martin (Politeknik Negeri Jember, 2023)
The in vitro study aimed to evaluate the utilization of maggot flour from selected substrates as a substitute for soybean meal in sheep rations on digestibility and rumen fermentation in vitro. Maggot were reared using three different substrates i.e., sheep feces, household waste and bread waste. The BSF maggot product with feces substrate showed the highest protein was used in this study. The treatments in this study were T1=100% soybean meal, T2=50% soybean meal + 50% maggot flour, T3=100% maggot flour. In vitro rumen fermentation and digestibility were conducted and the parameters were pH, NH3, volatile fatty acid (VFA), dry matter digestibility (DMD) and organic matter digestibility (OMD). Maggot rearing data were presented descriptively while the in vitro data were analyzed using analysis of variance. The result showed that the treatments had no significant effect (P>0.05) on pH, VFA, DMD and OMD, but replacement of soybean meal (100% maggot flour) affected NH3 production. The utilization of maggot as a substitute for soybean meal in sheep ration did not have a negative impact on in vitro fermentability and rumen digestibility.